Didactic Strategies by Competences for the Teaching of Biology in Undergraduate Students of the Specialty of Biology and Chemistry, Faculty of Education - Universidad Nacional Mayor de San Marcos - Blanco Ayala, Luis Fernando (2020)
The main objective of this article is to determine the influence between the variables: didactic strategies by competence in the teaching of biology in undergraduate students. According to the nature and characteristics of the research, it was strategically determined as a descriptive study, with a quantitative, quasi - experimental, ex - post - facto and explanatory approach. The sample consisted of students from semesters III to X, who are studying the different subjects of biology, in the specialty of Biology and Chemistry, according to the 2013 study plan of the Faculty of Education at the Universidad Nacional Mayor de San Marcos, the same that amount to 110 students. Two instruments were made, one for each study variable, with an internal consistency reliability according to the Cronbach ? Coefficient = 0.900 “excellent” value. SPSS v.25 was used for statistical treatment. The study confirmed that Didactic Strategies by Competences DO significantly influence the teaching of biology in undergraduate students of the specialty of Biology and Chemistry, Faculty of Education, at the Universidad Nacional Mayor de San Marcos.